Flexibility of habitat use in novel environments: insights from a translocation experiment with lesser black-backed gulls - van Toor ML; Arriero E; Holland RA; Huttunen MJ; Juvaste R; Muller I; Thorup K; Wikelski M; Safi K (ROYAL SOC, 2022)
Being faced with unknown environments is a concomitant challenge of species' range expansions. Strategies to cope with this challenge include the adaptation to local conditions and a flexibility in resource exploitation. The gulls of the Larus argentatus-fuscus-cachinnans group form a system in which ecological flexibility might have enabled them to expand their range considerably, and to colonize urban environments. However, on a population level both flexibility and local adaptation lead to signatures of differential habitat use in different environments, and these processes are not easily distinguished. Using the lesser black-backed gull (Larus fuscus) as a system, we put both flexibility and local adaptation to a test. We compare habitat use between two spatially separated populations, and use a translocation experiment duringwhich individuals were released into novel environment. The experiment revealed that on a population-level flexibility best explains the differences in habitat use between the two populations. We think that our results suggest that the range expansion and huge success of this species complex could be a result of its broad ecological niche and flexibility in the exploitation of resources. However, this also advises caution when using species distribution models to extrapolate habitat use across space.